PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF GOOGLE SITES “INDOWEBLEARN” UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR PESERTA DIDIK KELAS VI DI UPT SPF SD INPRES KAMPUS IKIP - Iga Ayu Mawarni Iga Ayu Mawarni; hasnawati hasnawati; Baharullah Baharullah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to improve the learning outcomes and learning motivation of class VI students at UPT SPF SD Inpres IKIP Campus by implementing the interactive learning media Google Sites "IndoWebLearn" in Indonesian language subjects. The type of research used is Classroom Action Research. The subjects in the research were class VI students at UPT SPF SD Inpres IKIP Campus with a total of 36 students consisting of 19 male students and 17 female students. The data collection techniques used were tests and non-tests, with tests in the form of choice questions. double with 15 questions and a non-test in the form of filling out a student learning motivation questionnaire. From the first cycle data, the average learning outcome value was 79.67 with a percentage of student completeness of 63.89%, while learning motivation was 30.55%. After learning in cycle II, learning outcomes increased with an average learning outcome score of 84.08 with a completion percentage of 89% while learning motivation was 91.67%. This indicates that the application of the interactive learning media Google Sites "IndoWebLearn" is effective in improving learning outcomes and learning motivation for class VI students at UPT SPF SD Inpres IKIP Campus.